PENGARUH KINERJA KEUANGAN TERHADAP NILAI PERUSAHAAN SEBAGAI MANIFESTASI PEMBELAJARAN INVESTASI - Listiadi, Agung (JURNAL EKONOMI PENDIDIKAN DAN KEWIRAUSAHAAN, 2015)
Companies that sell shares to the public in going public should have a good overview. A good overview is needed to gain the trust of investors. Companies in an effort to gain the confidence of investors will provide information that is credible. It characterizes the character of the company, especially on financial performance. To determine the effect of the financial performance of the company's value are used regression analysis techniques. The survey results a significant influence from the financial performance to the company's value. Effect on the financial performance to the company's value is 6%. This can be seen in the year 2006 the number of company which had financial performance above the average were 40%, while in 2007 rose to 42% and in 2008 it was 38%. This illustrates all investors still using ROE value in taking the decision to invest, when to invest in companies included in the list of LQ-45 the period 2006 to 2008